Penanggulangan Penyakit Kesurupan Jin: Analisis Konsep Pendidikan Kesehatan Rohani dalam Al-Qur’an - M. Kasim (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This study aims to analyze the concept of spiritual health education in the Qur'an in dealing with spiritual health disorders in the form of possession by a jinn. This research is a library research using descriptive method and analyzed using interpretation, syarḥ of hadith, pedagogical, philosophical and public health science approaches. The results of the research show that the Qur'an contains the concept of spiritual health education, in the form of preventive, curative (treatment), and maintenance of various spiritual diseases. The preventive concept aims to protect and fortify oneself from being infected with spiritual disorders/illness, while the curative concept aims to provide therapeutic measures if someone has been infected with a disease. The development of the concept of spiritual health education gave birth to a special concept for tackling jinn possessed, namely; a). The preventive method is carried out by: strengthening faith and piety, consistently carrying out His Shari'a, trusting, purifying monotheism, doing istiāżah (asking for protection from Allah), earnestly repenting, giving charity/loving to donate, always reading the Qur'an, zikr, pray and perform circumcision services; b). curative methods in the form of treatment measures for sufferers of jinn and possession disorders by using the Qur'anic method called ruqyah syar'iyyah, namely a therapeutic method by reciting verses from the Al-Qur'an and prayers that were passed down by the Prophet saw, and using treatment that is not contrary to Islamic law.